Collegiate athletes' perceptions of the culture of concussion reporting. Issue 4 (8th June 2021) - Kneavel, Meredith; Ernst, William; Brandsma, Lynn
Abstract: Objective: The current study was designed to understand the culture of concussion among college student-athletes. Participants: Eight men's lacrosse and seven women's soccer players. Methods: A focus group was conducted to understand thoughts, barriers, team culture, and what was needed to feel safe reporting symptoms. Thematic analysis was conducted to identify key themes. Results: Themes included concerns about being taken out, pushing through, wanting to play, severity influencing reporting, changes about concussion reporting, uncertainty about symptoms, concussion have changed the game, reporting a teammate, wanting someone else to make the call, desire to raise awareness, deception, wanting professors to have more understanding, circumstances influencing reporting, helmets specific for concussion, malingering, and the return to play protocol being too long. Conclusion: Factors ranging from intrinsic to more distal cultural and environmental factors appear to influence reporting concussions. Student-athletes identified factors unique to the college athlete environment.